Anomali Size Effect di Bursa Efek Indonesia - Ramel Yanuarta (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2012)
This study aims to find empirical evidence about the size effect phenomenon, that the smaller firms consistently generate higher stocks return than larger firms on average, in Indonesia Stock Exchange (IDX). My empirical evidences, which use data from LQ-45 within period of 2005-2007, show that the smaller firms do not generate higher return on based on market capitalization and value of total assets approach. Two different methods are used, i.e. paired sample t-test and market-adjusted regression model. Additional results show that stock portfolio of smaller firms are riskier than that of the bigger ones, based on the greater standard deviation value.